(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The research work was conducted in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur to identify the insect pollinators abundant in eggplant field, and to know the effect of insect pollinators and pests on the yield and seed quality of the crop. Eggplants were cultivated in three conditions viz., open, enclosed in net without supplemented insect pollination, and enclosed in net with supplemented insect pollination. In total 8 species of insects belonged to 6 families in 3 orders were found as pollinator on eggplant and their abundance varied from 0.6±0.1 to 1.6±0.3 /30 sweeps. Among the pollinator insects, ant showed the highest abundance and longest foraging duration per flower. The plant infestation among the treatments varied from 2.6±2.6 to 12.8±1.6% and the highest and the lowest levels were observed in open condition and enclosed condition respectively. The fruit infestation ranged from 11.3±1.6 to 43.7±3.0% and the highest infestation was observed in open condition. Insect pollination produced the higher number of fruits per plant (14.4±0.4/plant) as well as larger fruits (length: 27.6±0.7 cm and breadth: 11.6±0.2 cm), and thus produced higher yield (11.6±0.4 tha-1) and higher germination (82.0± 2.5%) of seeds. Bangladesh J. Agril. Res. 44(1): 103-113, March 2019